Changes in Facial Asymmetry following Chuna Manual Therapy-Centered Korean Medicine Treatment: A Retrospective Case Series of Four Patients - Eunho Jeong; Hoyeong Seong; Hyun-Jong Jung (Journal of Korean Medicine, 2026)
Objectives: This study aimed to describe the treatment course and observed changes in patients with facial asymmetry who received Chuna Manual Therapy (CMT)-centered Korean Medicine (KM) treatment.Methods: This retrospective case series analyzed clinical records of four patients treated between January 2024 and April 2026. Eligible patients had no history of acute facial trauma or surgery, received no concurrent treatment for facial asymmetry, completed treatment, had complete pre- and post-treatment data, and provided written informed consent. Treatment consisted of CranioSacral Therapy, Facial, Cervical, and Pelvic CMT, and acupuncture. Patients attended every 1–2 weeks, with each session lasting approximately 1 hour; the treatment duration and number of sessions varied among patients. Treatment sites and stimulation intensity were individualized according to each patient’s condition. Acupoints selected based on anatomical location and meridian theory included BL2, ST7, ST4, etc. Outcomes were evaluated using facial photographs, 3D Morpheus, cephalometric radiographs, and a patient-reported outcome questionnaire.Results: Following treatment, changes in more symmetrical facial tilt indices were observed across all cases. Changes in reduced 3D Morpheus curved length deviations and more symmetrical skeletal indices were also observed. PROM assessments indicated reductions in temporomandibular joint pain/clicking, limited mouth opening, and neck/shoulder discomfort, and pelvic misalignment.Conclusions: CMT-centered KM treatment was followed by changes in facial tilt, soft-tissue symmetry, skeletal alignment, and associated symptoms. However, given the small, uncontrolled retrospective design and individualized co-interventions, efficacy and causality cannot be established. Further controlled studies are warranted.